Advanced courses of mathematical analysis I : (World Scientific, 2004)
This volume consists of a collection of articles from experts with a rich research and educational experience. The contributors of this volume are: Y Benyamini, M González, V Müller, S Reich, E Matouskova, A J Zaslavski and A R Palacios. Each of their work is invaluable. For example, Benyamini’s is the only updated survey of the exciting and active area of the classification of Banach spaces under uniformly continuous maps while González’s article is a pioneer introduction to the theory of local duality for Banach spaces.